2004
DOI: 10.1051/0004-6361:20040231
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of thermonuclear shell sources in stars

Abstract: Abstract. We present a quantitative criterion for the thermal stability of thermonuclear shell sources. We find that the thermal stability of shell sources depends on exactly three factors: they are more stable when they are geometrically thicker, less degenerate and hotter. This confirms and unifies previously obtained results in terms of the geometry, temperature and density of the shell source, by a simplified but quantitative approach to the physics of shell nuclear burning. We present instability diagrams… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 25 publications
1
54
0
Order By: Relevance
“…A more recent study of accretion onto WDs can be found in Yoon, Langer, and van der Sluys. 39 Examining their work, the calculations done with NOVA are initially in their stable regime but evolve into instability.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study of accretion onto WDs can be found in Yoon, Langer, and van der Sluys. 39 Examining their work, the calculations done with NOVA are initially in their stable regime but evolve into instability.…”
Section: Discussionmentioning
confidence: 99%
“…In sequence NR4, the mean temperature in the shell source remains nearly constant, around T 2.02 × 10 8 K during the stable shell burning phase. Figure 9 shows the border between stability and instability for T = 2 × 10 8 K, as obtained by Yoon et al (2004), as a dotted line. The shell source becomes more degenerate and thinner as the white dwarf mass grows, and finally enters the unstable regime when M WD 1.03 M , resulting in the onset of thermal pulses as shown in Fig.…”
Section: Stability Of Helium Shell Burningmentioning
confidence: 98%
“…To understand the behavior of increasing L crit for higher values ofṀ, we follow the stability analysis of thermonuclear burning in a thin shell by Giannone & Weigert (1967) (see also Yoon et al 2004b). These authors derive an expression for the inverse of the growth timescale of temperature perturbations, τ −1 pert , by considering both thermonuclear burning and radiative cooling (Eq.…”
Section: Mass Accretion Rate Dependencementioning
confidence: 99%